Nonaqueous electrolyte containing additive for nonaqueous electrolyte and lithium secondary battery containing the same
A coumarin-based additive in the non-aqueous electrolyte forms a stable SEI film, addressing metal ion elution and enhancing lithium secondary battery performance at low temperatures.
Patent Information
- Application Number
- JP2023565561
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-06
- Filing Date
- 2022-08-05
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-08-05
AI Technical Summary
Lithium secondary batteries face issues with metal ion elution leading to electrode deterioration and reduced stability, especially at low temperatures, affecting capacity and lifespan.
Incorporation of a coumarin-based additive in the non-aqueous electrolyte that forms a stable, low-resistance SEI film on the electrode surfaces, suppressing interfacial reactions and enhancing ion transport.
The additive improves the battery's storage characteristics and cycle life by forming a low-resistance film, maintaining capacity and reducing electrode degradation at low temperatures.
Smart Images

Figure 0007616788000001 
Figure 0007616788000002 
Figure 0007616788000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0103601 filed on August 6, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.
[0002] The present invention relates to a non-aqueous electrolyte containing an additive for a non-aqueous electrolyte, and a lithium secondary battery containing the same. [Background technology]
[0003] In recent years, the application areas of lithium secondary batteries have been rapidly expanding from power supply for electronic devices such as electrical, electronic, communication, and computer devices to power storage and supply for large-area devices such as automobiles and power storage devices. Accordingly, there is an increasing demand for high-capacity, high-output, and highly stable secondary batteries.
[0004] In particular, high capacity, high output, and long life characteristics are important for lithium secondary batteries for automotive applications. To increase the capacity of secondary batteries, positive electrode active materials with high nickel content, which have high energy density but low stability, are used, or secondary batteries are operated at high voltage.
[0005] However, when a secondary battery is operated under the above conditions, as charging and discharging proceeds, the coating formed on the surface of the positive / negative electrode or the structure of the electrode surface may deteriorate due to side reactions caused by the deterioration of the electrolyte, and transition metal ions may be eluted from the surface of the positive electrode. In this way, the eluted transition metal ions are electro-deposited on the negative electrode, which reduces the passivation ability of the SEI, causing the problem of the deterioration of the negative electrode.
[0006] In addition, for lithium secondary batteries for automotive applications, high capacity, high output, and long life characteristics are important even at room temperature and low temperature regions. However, at room temperature and low temperature regions, the ion transfer characteristics decrease, resulting in a problem of decreased capacity characteristics and life characteristics.
[0007] Therefore, in order to solve these problems, research and development efforts are being conducted to find a method for forming a low-resistance SEI coating that suppresses the elution of metal ions in the positive electrode and has high ion transport properties. Summary of the Invention [Problem to be solved by the invention]
[0008] As a result of conducting extensive research to solve the above problems, an object of the present invention is to provide an additive for a non-aqueous electrolyte that can suppress deterioration of a positive electrode, reduce side reactions between a positive electrode and an electrolyte, and form a stable and low-resistance SEI film on a negative electrode.
[0009] Another object of the present invention is to provide a non-aqueous electrolyte containing the additive for a non-aqueous electrolyte, and thereby improving the life characteristics.
[0010] Another object of the present invention is to provide a lithium secondary battery containing the non-aqueous electrolyte, which has improved storage characteristics and cycle characteristics, and thus improved performance. [Means for solving the problem]
[0011] According to one embodiment, in order to achieve the above object, the present invention provides a non-aqueous electrolyte comprising an additive for a non-aqueous electrolyte represented by the following Chemical Formula 1:
[0012] [ka]
[0013] In the above Chemical Formula 1, R1 to R5 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms; R x may be an alkyl group having 1 to 10 carbon atoms substituted with at least one fluoro group, or an alkoxy group having 1 to 10 carbon atoms substituted with at least one fluoro group.
[0014] According to another embodiment, the present invention provides a lithium secondary battery including the non-aqueous electrolyte. Effect of the Invention
[0015] The compound represented by Chemical Formula 1, which is provided as an additive for non-aqueous electrolytes according to the present invention, is a compound based on a coumarin structure and can form a stable SEI (Solid Electrolyte Interphase) film on the surface of the negative electrode while being rapidly reductively decomposed during charging and discharging, and the film formed at this time can have low resistance characteristics. Since ion transfer characteristics decrease in the room temperature and low temperature regions, the resistance state of the film is a factor that determines the life and capacity performance, but when the additive for non-aqueous electrolytes according to the present invention, which forms a relatively low resistance film, is used, the room temperature / low temperature characteristics can be improved.
[0016] In addition, the compound represented by Chemical Formula 1, which is provided as an additive for a non-aqueous electrolyte of the present invention, contains, in addition to the coumarin structure, at least one alkyl or alkoxy group substituted with a fluoro group, and thus can form a coating rich in inorganic substances such as LiF on the positive and negative electrodes, thereby suppressing deterioration due to interface reactions.
[0017] Therefore, when the nonaqueous electrolyte of the present invention containing the compound of Chemical Formula 1 is used, an electrode-electrolyte interface having low resistance can be formed, thereby realizing a lithium secondary battery having improved storage characteristics, resistance characteristics, and cycle characteristics at low and room temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0019] As used herein, terms such as "comprise," "comprise," or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but should not be understood as precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0020] In the present specification, in the description of "carbon number a to b", "a" and "b" refer to the number of carbon atoms contained in a specific functional group. That is, the functional group may contain "a" to "b" carbon atoms. For example, "an alkylene group having 1 to 5 carbon atoms" refers to an alkylene group having 1 to 5 carbon atoms, i.e., -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2CH(CH3)-, -CH(CH3)CH2-, -CH(CH3)CH2CH2-, etc. In addition, in the present specification, any alkyl group may be substituted or unsubstituted. The term "substituted" means that, unless otherwise defined, at least one hydrogen atom bonded to a carbon atom is replaced with an element other than hydrogen, and means that the alkyl group has 1 to 20 carbon atoms, the alkenyl group has 2 to 20 carbon atoms, the alkynyl group has 2 to 20 carbon atoms, the alkoxy group has 1 to 20 carbon atoms, the cycloalkyl group has 3 to 12 carbon atoms, the cycloalkenyl group has 3 to 12 carbon atoms, the heterocycloalkyl group has 3 to 12 carbon atoms, the heterocycloalkenyl group has 3 to 12 carbon atoms, the aryloxy group has 6 to 12 carbon atoms, a halogen atom, a fluoroalkyl group having 1 to 20 carbon atoms, a nitro group, a nitrile group, an aryl group having 6 to 20 carbon atoms, a heteroaryl group having 2 to 20 carbon atoms, a haloaryl group having 6 to 20 carbon atoms, or the like.
[0021] The present invention will now be described in more detail.
[0022] Nonaqueous electrolyte The non-aqueous electrolyte according to an embodiment of the present invention includes a compound represented by the following formula 1 as an additive. The compound represented by the following formula 1 is a compound based on a coumarin structure, and can form a stable SEI (Solid Electrolyte Interphase) coating on the surface of the negative electrode while being rapidly reductively decomposed during charging and discharging, and the coating formed at this time can have low resistance properties.
[0023] [ka]
[0024] In the above Chemical Formula 1, R1 to R5 may each independently be any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms, preferably any one selected from the group consisting of H, an alkyl group having 1 to 5 carbon atoms, and an alkoxy group having 1 to 5 carbon atoms, and most preferably H.
[0025] In the above formula 1, R x may be an alkyl group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups, or an alkoxy group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups. By including an alkyl group or an alkoxy group substituted with a fluoro group in the coumarin structure, a dense coating can be formed on the electrode, which has the effect of suppressing deterioration due to an interfacial reaction.
[0026] Preferably, in the above formula 1, R x may be CF3, an alkyl group or an alkoxy group substituted with CF3. xmay be any one selected from CF3, an alkyl group having 1 to 9 carbon atoms substituted with CF3, OCF3, and an alkoxy group having 1 to 9 carbon atoms substituted with CF3. When substituted with CF3, a coating rich in inorganic substances such as LiF is formed on the positive and negative electrodes, which has the effect of suppressing deterioration due to interface reactions.
[0027] Most preferably, in the above formula 1, R x may be any one selected from CF3 and an alkyl group having 1 to 4 carbon atoms substituted with CF3.
[0028] Specifically, the compound represented by Chemical Formula 1 of the present invention may be a compound represented by Chemical Formula 1-1 below.
[0029] [ka]
[0030] In the above Chemical Formula 1-1, R x may be an alkyl group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups, or an alkoxy group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups. By further including an alkyl group or an alkoxy group substituted with a fluoro group in the coumarin structure, a dense coating can be formed on the electrode, which has the effect of suppressing deterioration due to an interface reaction. Preferably, in the above chemical formula 1-1, R x may be any one selected from CF3, an alkyl group having 1 to 9 carbon atoms substituted with CF3, and an alkoxy group having 1 to 9 carbon atoms substituted with CF3. x may be any one selected from CF3 and an alkyl group having 1 to 4 carbon atoms substituted with CF3. When substituted with CF3, a coating rich in inorganic substances such as LiF is formed on the positive and negative electrodes, which has the effect of suppressing deterioration due to interface reactions.
[0031] Specifically, the compound represented by Chemical Formula 1 of the present invention may be any one of the compounds represented by Chemical Formulas 2-1 to 2-7 below.
[0032] [ka]
[0033] [ka]
[0034] [ka]
[0035] [ka]
[0036] [ka]
[0037] [ka]
[0038] [ka]
[0039] In the present invention, the additive for the non-aqueous electrolyte may be included in an amount of 0.01 to 3 parts by weight, preferably 0.1 to 2 parts by weight, more preferably 0.5 to 1.0 parts by weight, based on 100 parts by weight of the non-aqueous electrolyte. If the content of the compound represented by Chemical Formula 1 is less than 0.01 parts by weight, the positive / negative electrode film formation effect may become insignificant as the driving time increases, and the effect of suppressing the elution of transition metals may decrease. In addition, if the content of the compound represented by Chemical Formula 1 exceeds 3 parts by weight, not only the viscosity of the electrolyte may increase due to an excessive amount of additive, but also the ion conductivity may decrease due to the increased viscosity, which may adversely affect the mobility of ions in the battery, thereby causing a decrease in rate characteristics and life characteristics. In addition, excessive decomposition of the additive may increase the battery resistance and cause side reactions and by-products.
[0040] The non-aqueous electrolyte according to the present invention may further comprise a lithium salt, an organic solvent, and optionally other electrolyte additives.
[0041] The lithium salt is used as an electrolyte salt in a lithium secondary battery and is used as a medium for transferring ions. Generally, the lithium salt contains, for example, Li as a cation. + and as an anion, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO2 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N -, (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - , and SCN - The present invention includes at least one selected from the group consisting of:
[0042] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide; LiFSI), LiN(SO2CF2CF3)2 (lithium bis(perfluoroethanesulfonyl)imide; LiBETI), and LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide; LiTFSI). In addition to these, any lithium salt commonly used in the electrolyte of a lithium secondary battery can be used without any restrictions.
[0043] The lithium salt can be appropriately changed within a range that can be normally used, but in order to obtain an optimal effect of forming a corrosion prevention coating on the electrode surface, it may be contained in the electrolyte at a concentration of 0.5 M to 5.0 M, preferably 0.8 M to 2.5 M, and more preferably 1.0 M to 2.0 M. If the concentration of the lithium salt is less than 0.5 M, the amount of lithium is insufficient, resulting in deterioration of the capacity and cycle characteristics of the lithium secondary battery, and if the concentration exceeds 5.0 M, there is a risk of problems such as a decrease in electrolyte impregnation due to an increase in the viscosity of the non-aqueous electrolyte, a decrease in ion conductivity, and an increase in battery resistance.
[0044] The non-aqueous organic solvent may include at least one organic solvent selected from the group consisting of cyclic carbonate organic solvents, linear carbonate organic solvents, linear ester organic solvents, and cyclic ester organic solvents.
[0045] Specifically, the organic solvent may include a cyclic carbonate organic solvent, a linear carbonate organic solvent, or a mixture thereof.
[0046] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and can effectively dissociate the lithium salt in the electrolyte. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and among these, ethylene carbonate may be included.
[0047] The linear carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and a representative example thereof may be at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).
[0048] In addition, in order to produce an electrolyte having high ionic conductivity, the organic solvent may further contain at least one or more ester-based organic solvents selected from the group consisting of linear ester-based organic solvents and cyclic ester-based organic solvents in addition to the at least one or more carbonate-based organic solvents selected from the group consisting of cyclic carbonate-based organic solvents and linear carbonate-based organic solvents.
[0049] Specific examples of such linear ester-based organic solvents include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0050] The cyclic ester organic solvent may be at least one organic solvent selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0051] Meanwhile, the organic solvent may be, if necessary, an organic solvent that is generally used in non-aqueous electrolytes without limitation, and may further include at least one of an ether-based organic solvent, a glyme-based solvent, and a nitrile-based organic solvent.
[0052] The ether solvent may be any one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL), and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more of these, but is not limited thereto.
[0053] The glyme-based solvent has a higher dielectric constant and lower surface tension than linear carbonate-based organic solvents and is less reactive with metals, and may include at least one selected from the group consisting of dimethoxyethane (glyme, DME), diethoxyethane, diglyme, triglyme, and tetraglyme (TEGDME), but is not limited thereto.
[0054] The nitrile-based solvent may be one or more selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile, but is not limited thereto.
[0055] In addition, the nonaqueous electrolyte of the present invention may further contain a known electrolyte additive, as necessary, in order to prevent the nonaqueous electrolyte from being decomposed in a high-output environment, which would cause the collapse of the negative electrode, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and the effect of suppressing battery expansion at high temperatures.
[0056] Representative examples of such other electrolyte additives may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0057] Examples of the cyclic carbonate compounds include vinylene carbonate (VC) and vinyl ethylene carbonate.
[0058] An example of the halogen-substituted carbonate compound is fluoroethylene carbonate (FEC).
[0059] The sultone compound includes at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0060] The sulfate compounds include ethylene sulfate (Esa), trimethylene sulfate (TMS), and methyl trimethylene sulfate (MTMS).
[0061] The phosphate-based compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, trimethylsilylphosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.
[0062] Examples of the borate-based compounds include tetraphenylborate, lithium oxalyl difluoroborate (LiODFB), and lithium bis(oxalate)borate (LiB(C2O4)2, LiBOB).
[0063] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0064] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.
[0065] The lithium salt-based compound is a compound different from the lithium salt contained in the non-aqueous electrolyte, and examples of the lithium salt-based compound include lithium difluorophosphate (LiDFP), LiPO2F2, and LiBF4.
[0066] Among these other electrolyte additives, when a combination of vinylene carbonate (VC), 1,3-propane sultone (PS), ethylene sulfate (Esa), and lithium difluorophosphate (LiDFP) is further included, a stronger SEI film can be formed on the surface of the negative electrode during the initial activation process of the secondary battery, and the generation of gas that may be generated by decomposition of the electrolyte at high temperatures can be suppressed, thereby improving the high temperature stability of the secondary battery.
[0067] Meanwhile, the other electrolyte additives may be used in a mixture of two or more kinds, and may be included in an amount of 0.01 to 20% by weight, specifically 0.01 to 10% by weight, preferably 0.05 to 5% by weight, based on the total weight of the non-aqueous electrolyte. If the content of the other electrolyte additives is less than 0.01% by weight, the effect of improving the high-temperature storage characteristics and high-temperature life characteristics of the battery is small, and if the content of the other electrolyte additives exceeds 20% by weight, excessive side reactions may occur in the electrolyte during charging and discharging of the battery. In particular, if the other electrolyte additives are added in an excessive amount, they may not be sufficiently decomposed at high temperatures and may exist in the electrolyte at room temperature as unreacted or precipitated. This may cause side reactions that reduce the life or resistance characteristics of the secondary battery.
[0068] Lithium secondary battery The present invention also provides a lithium secondary battery containing the non-aqueous electrolyte.
[0069] Specifically, the lithium secondary battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and the non-aqueous electrolyte.
[0070] In this regard, the lithium secondary battery of the present invention may be manufactured by a conventional method known in the art, for example, by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator are sequentially stacked between the positive electrode and the negative electrode, and then inserting the electrode assembly into a battery case and injecting the non-aqueous electrolyte according to the present invention into the battery case.
[0071] (1) Positive electrode The positive electrode may be prepared by coating a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, and a solvent on a positive electrode current collector.
[0072] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. may be used.
[0073] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specifically, it may include a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium metal oxide may be a lithium-manganese-based oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-manganese-cobalt-based oxide (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.), or a lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mnr3 M S2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are atomic fractions of independent elements, respectively, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, and p2 + q2 + r3 + s2 = 1), etc.) etc. may be mentioned, and one or more of these compounds may be included.
[0074] Among them, from the viewpoint of being able to enhance the capacity characteristics and stability of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.). Also, considering the significance of the improvement effect by controlling the types and content ratios of the constituent elements forming the lithium composite metal oxide, the lithium composite metal oxide is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., and one or more of these mixtures may be used.
[0075] Among them, a positive electrode active material having a nickel content of 80 atm% or more can be used because it can maximize the capacity characteristics of the battery. For example, the lithium transition metal oxide may include one represented by the following chemical formula 3.
[0076] [Chemical formula 3] Li x Ni a Co b M 1 c M 2 d O2
[0077] In the above Chemical Formula 3, M 1 is one or more selected from Mn and Al, and may be preferably Mn, or a combination of Mn and Al.
[0078] M 2 may be one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.
[0079] The x represents the atomic fraction of lithium in the lithium transition metal oxide, and may be 0.90≦x≦1.1, preferably 0.95≦x≦1.08, and more preferably 1.0≦x≦1.08.
[0080] The a represents the atomic fraction of nickel among the metal elements other than lithium in the lithium transition metal oxide, and may be 0.80≦a<1.0, preferably 0.80≦a≦0.95, and more preferably 0.80≦a≦0.90. When the nickel content satisfies the above range, high capacity characteristics can be achieved.
[0081] The b represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium transition metal oxide, and is 0. <b<0.2、0<b≦0.15、または0.01≦b≦0.10であってもよい。
[0082] The c is M among the metal elements other than lithium in the lithium transition metal oxide. 1 represents the atomic fraction of 0 <c<0.2、0<c≦0.15、または0.01≦c≦0.10であってもよい。
[0083] The d is the number of metal elements other than lithium in the lithium transition metal oxide, M 2 and may be 0≦d≦0.1, or 0≦d≦0.05.
[0084] The positive electrode active material may be contained in an amount of 60 to 99% by weight, preferably 70 to 99% by weight, and more preferably 80 to 98% by weight, based on the total weight of the solid content in the positive electrode mixture slurry.
[0085] The binder is a component that assists in binding the active material and conductive material and the like to the current collector.
[0086] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene, sulfonated ethylene-propylene-diene, styrene-butadiene rubber, fluororubber, various copolymers, and the like.
[0087] Generally, the binder may be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of the solid content in the positive electrode mixture slurry.
[0088] The conductive material is a component for further improving the conductivity of the positive electrode active material.
[0089] The conductive material is a component for further improving the conductivity of the positive electrode active material, and may be added in an amount of 1 to 20% by weight based on the total weight of the solid content in the positive electrode slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite; conductive fibers such as carbon fiber, carbon nanotube, and metal fiber; carbon fluoride powder; conductive powder such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0090] Generally, the conductive material may be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of the solid content in the positive electrode mixture slurry.
[0091] The solvent may contain an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the positive electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the solvent may be contained so that the concentration of the solid content including the positive electrode active material, and optionally a binder and a conductive material, is 50 to 95% by weight, preferably 70 to 95% by weight, and more preferably 70 to 90% by weight.
[0092] (2) Negative electrode The negative electrode can be prepared by coating a negative electrode mixture slurry containing a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode current collector, or a graphite electrode made of carbon (C) or a metal itself can be used as the negative electrode.
[0093] For example, when the negative electrode is produced by coating the negative electrode mixture slurry on the negative electrode current collector, the negative electrode current collector generally has a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, as with the positive electrode current collector, the binding force of the negative electrode active material may be strengthened by forming fine irregularities on the surface, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric body, etc.
[0094] The negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of such a metal and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0095] The carbonaceous material capable of reversibly intercalating / deintercalating lithium ions may be any carbonaceous negative electrode active material commonly used in lithium ion secondary batteries, and representative examples thereof include crystalline carbon, amorphous carbon, or a combination of both. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, and calcined coke.
[0096] As the metal or an alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium can be used.
[0097] As the metal composite oxide, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, elements of Group 1, Group 2, Group 3 of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) selected from the group consisting of can be used.
[0098] As the substance capable of doping and undoping lithium, Si, SiO x (0 < x ≦ 2), Si-Y alloy (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and a combination thereof, and is not Si), Sn, SnO2, Sn-Y (wherein Y is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, and a combination thereof, and is not Sn), etc. can be mentioned, and at least one of these and SiO2 may be mixed and used. The element Y may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and a combination thereof.
[0099] Examples of the transition metal oxide include lithium-containing titanium oxide (LTO), vanadium oxide, and lithium vanadium oxide.
[0100] The negative electrode active material may be contained in an amount of 60 to 99% by weight, preferably 70 to 99% by weight, and more preferably 80 to 98% by weight, based on the total weight of the solid content in the negative electrode mixture slurry.
[0101] The binder is a component that assists in binding between the conductive material, the active material, and the current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene, sulfonated ethylene-propylene-diene, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0102] Generally, the binder may be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of the solid content in the negative electrode mixture slurry.
[0103] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1 to 20% by weight based on the total weight of the solid content in the negative electrode slurry. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite; conductive fibers such as carbon nanotubes, carbon fibers, or metal fibers; carbon fluoride powder; conductive powder such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.
[0104] The conductive material may be contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of the solid content in the negative electrode mixture slurry.
[0105] The solvent may contain water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the negative electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the solvent may be contained so that the concentration of the solid content including the negative electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, preferably 70% by weight to 90% by weight.
[0106] When a metal is used as the negative electrode, the negative electrode can be manufactured by physically bonding, rolling, or depositing a metal on a metal thin film or the negative electrode current collector. The deposition method can be an electrical deposition or chemical vapor deposition method.
[0107] For example, the metal thin film itself or the metal bonded / rolled / deposited onto the negative electrode current collector may include one metal or an alloy of two metals selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu), and indium (In).
[0108] (3) Separator In addition, the separator may be a conventional porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, which is used alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, etc., which is used as a separator, but is not limited thereto. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or a multilayer structure.
[0109] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0110] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely illustrative for understanding the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description, and it goes without saying that such changes and modifications belong to the scope of the attached claims.
[0111] Working Example Example 1 (Production of non-aqueous electrolyte) A non-aqueous solvent was prepared by dissolving LiPF6 at 1.0M, vinylene carbonate (VC) at 0.5 wt%, 1,3-propane sultone (PS) at 0.5 wt%, ethylene sulfate (Esa) at 1.0 wt%, and lithium difluorophosphate (LiDFP) at 0.8 wt% in an organic solvent (ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3: 7 volume ratio), and 0.5 g of 1-trifluoroacetylcoumarin (compound of formula 2-1) was added to 99.5 g of the non-aqueous solvent to prepare a non-aqueous electrolyte.
[0112] (Manufacture of lithium secondary batteries) Cathode active material (LiNi 0.85 Co 0.05 Mn 0.07 Al 0.03 A cathode slurry (solid content 76.5 wt%) was prepared by adding the cathode (O2), conductive material (carbon nanotubes), and binder (polyvinylidene fluoride) in a weight ratio of 98.0:0.7:1.3 to the solvent N-methyl-2-pyrrolidone (NMP). The cathode slurry was applied to one side of a cathode current collector (aluminum thin film) with a thickness of 12 μm, and dried and roll pressed to prepare a cathode.
[0113] A negative electrode active material (artificial graphite), a conductive material (carbon black), and a binder (styrene-butadiene rubber) were mixed in a weight ratio of 96.5:1.5:2.0 with distilled water as a solvent to prepare a negative electrode slurry (solid content 50% by weight). The negative electrode slurry was applied to one side of a negative electrode current collector (Cu thin film) with a thickness of 8 μm, and dried and roll pressed to prepare a negative electrode.
[0114] A polyethylene porous film separator was interposed between the positive electrode and the negative electrode in a dry room, and the non-aqueous electrolyte was then injected therein to prepare a secondary battery.
[0115] Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that 1.0 g of 1-trifluoroacetylcoumarin (a compound represented by Formula 2-1) was added to 99.0 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0116] Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that 2.0 g of 1-trifluoroacetylcoumarin (a compound represented by Formula 2-1) was added to 98.0 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0117] Example 4 A secondary battery was manufactured in the same manner as in Example 1, except that 3.0 g of 1-trifluoroacetylcoumarin (a compound represented by Formula 2-1) was added to 97.0 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0118] Comparative Example 1 A secondary battery was manufactured in the same manner as in Example 1, except that a non-aqueous electrolyte was prepared using 100 g of the non-aqueous solvent prepared in Example 1.
[0119] Comparative Example 2 A secondary battery was manufactured in the same manner as in Example 1, except that 0.5 g of 1-trifluoromethylcoumarin (a compound represented by the following formula A) was added to 99.5 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0120] [ka]
[0121] Comparative Example 3 A secondary battery was manufactured in the same manner as in Example 1, except that 1.0 g of 1-trifluoromethylcoumarin (the compound represented by Formula A) was added to 99.0 g of the nonaqueous solvent prepared in Example 1 to prepare a nonaqueous electrolyte.
[0122] Comparative Example 4 A secondary battery was manufactured in the same manner as in Example 1, except that 0.5 g of 1-acetylcoumarin (a compound represented by the following formula B) was added to 99.5 g of the non-aqueous solvent prepared in Example 1 to prepare a non-aqueous electrolyte.
[0123] [ka]
[0124] Experimental Example 1: Evaluation of low-temperature capacitance characteristics For each of the secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 4, the low-temperature capacity characteristics were evaluated.
[0125] Specifically, the batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 were charged at 0° C. with a constant current of 0.33 C to 4.2 V, and then discharged with a constant current of 0.33 C to 3.0 V, and the discharge capacity was measured to compare the low-temperature capacity characteristics. The results are shown in Table 1 below.
[0126] [Table 1]
[0127] As shown in Table 1, it can be seen that Examples 1 to 4, which used the additive for non-aqueous electrolyte of the present invention, have higher low-temperature discharge capacity than Comparative Examples 1 to 4, which did not use the additive. This is believed to be because the additive for non-aqueous electrolyte of the present invention formed a coating with low resistance at low temperatures.
[0128] Experimental Example 2: Evaluation of cycle characteristics The cycle characteristics of each of the secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 4 were evaluated.
[0129] Specifically, each of the batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 was charged at 25° C. with a constant current of 0.33 C to 4.2 V and discharged with a constant current of 0.33 C to 3.0 V as one cycle, and then the capacity after the cycles was measured and the capacity retention rate relative to the initial capacity was calculated. The results are shown in Table 2 below.
[0130] [Table 2]
[0131] As shown in Table 2, it can be confirmed that Examples 1 to 4, in which the additive for non-aqueous electrolytes of the present invention was used, had a higher capacity retention rate than Comparative Examples 1 to 4, in which the additive was not used.
Claims
1. A non-aqueous electrolyte comprising an additive for a non-aqueous electrolyte represented by the following chemical formula 1: 【Chemistry 1】 (In the above Chemical Formula 1, R 1 ~R 5 are each independently any one selected from the group consisting of H, an alkyl group having 1 to 10 carbon atoms, and an alkoxy group having 1 to 10 carbon atoms; R x is an alkyl group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups, or an alkoxy group having 1 to 10 carbon atoms substituted with at least one or more fluoro groups.
2. The R x CF 3 , C.F. 3 an alkyl group having 1 to 9 carbon atoms substituted with OCF 3 , and C.F. 3 2. The nonaqueous electrolyte according to claim 1, wherein the alkoxy group is any one selected from the group consisting of an alkoxy group having 1 to 9 carbon atoms substituted with one of the following:
3. The R x CF 3 , and C.F. 3 2. The non-aqueous electrolyte according to claim 1, wherein the alkyl group is any one selected from the group consisting of alkyl groups having 1 to 4 carbon atoms substituted with one of the following:
4. The non-aqueous electrolyte according to claim 1, wherein the additive for a non-aqueous electrolyte represented by Chemical Formula 1 is an additive for a non-aqueous electrolyte represented by the following Chemical Formula 1-1: 【Chemistry 2】 (In the above Chemical Formula 1-1, R x CF 3 , C.F. 3 an alkyl group having 1 to 9 carbon atoms substituted with OCF 3 , and C.F. 3 is any one selected from the group consisting of an alkoxy group having 1 to 9 carbon atoms substituted with
5. The non-aqueous electrolyte according to claim 1, wherein the additive for the non-aqueous electrolyte represented by Chemical Formula 1 is any one of compounds represented by the following Chemical Formulas 2-1 to 2-7. 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】 【Chemistry 9】
6. The non-aqueous electrolyte according to claim 1, wherein the additive for the non-aqueous electrolyte is contained in an amount of 0.01 to 3 parts by weight per 100 parts by weight of the non-aqueous electrolyte.
7. 10. The non-aqueous electrolyte of claim 1 further comprising a lithium salt and an organic solvent.
8. The lithium salts are LiCl, LiBr, LiI, LiBF 4 , LiClO 4 , LiB 10 C 10 , LiAlCl 4 , LiAlO 2 , LiPF 6 , LiCF 3 SO 3 , LiCH 3 CO 2 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiCH 3 SO 3 , LiN(SO 2 F) 2 , LiN(SO 2 CF 2 CF 3 ) 2 , and LiN(SO 2 CF 3 ) 2 The non-aqueous electrolyte according to claim 7, wherein the non-aqueous electrolyte is one or more selected from the group consisting of:
9. The non-aqueous electrolyte according to claim 7 , wherein the lithium salt is contained at a concentration of 0.5 M to 5.0 M.
10. 8. The nonaqueous electrolyte according to claim 7, wherein the organic solvent includes at least one organic solvent selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, and a cyclic ester organic solvent.
11. A lithium secondary battery comprising the non-aqueous electrolyte according to claim 1 .
Citation Information
Patent Citations
Non-aqueous electrolyte for lithium ion battery, and lithium ion battery
CN102569889A
Non-aqueous electrolyte secondary battery
JP1998050344A
Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery containing the same
JP2022534525A
Cited By
Non-aqueous electrolyte and lithium secondary battery comprising the same
JP2026063308A